A review on aloe vera gel as edible coating on postharvest activities of fruits / Nur Syafiqah Idzreen Mohd Azam ... [et al.] - Mohd Azam, Nur Syafiqah Idzreen; Tan, Eddie Ti Tjih; Mohammad Noor, Nur Rabiatul Adawiah; Abdul Muttalib, Siti Azima (2021)
Postharvest activity is a key factor that affects the loss of nutritional and quality of fruits which consequently led to agricultural wastage. Therefore, edible coating from polysaccharide- based is widely used to overcome this issue as they act as protective barrier on the fruit's surface against microbial, enzymatic and chemical spoilage. Hence, aloe vera gel (AG) is extensively used as edible coating to provide an optimum preservation effect of fruits. So far, there has been little discussion about the studies of functional properties of AG. This review aims to describe the effectiveness of AG as edible fruits coating concerning the protective barrier and antioxidant agent against the postharvest activity. The findings from this review unveil that the good coating properties of AG is due to the glucomannans that can act both as gel (barrier) and antioxidant agent. On the other side, this study also bring to light regarding the potential toxicity by anthraquinone (aloe-emodin) compound in AG on human health.